2023
DOI: 10.26434/chemrxiv-2023-47d99
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Boundary Conditions for Promotion versus Poisoning in Copper-Gallium-based CO2–to–Methanol Hydrogenation Catalysts

Abstract: To establish descriptors for the activity of Cu-Ga-based CO2-to-methanol hydrogenation catalysts, we prepared via co-grafting followed by a reduction in hydrogen, a series of materials containing 3-6 nm Cu1-xGax alloyed nanoparticles with variable xGa. They display a volcano-type activity behavior, where methanol formation is promoted for xGa < 0.13, while above poisoning effects are observed. In catalysts that are prepared via different methods and differ in the degree of Ga reduction, only the fraction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
(57 reference statements)
1
2
0
Order By: Relevance
“…These results indicated that the Ni–Ga alloy nanoparticles retained their structure and composition under CO 2 hydrogenation conditions, with no evidence for dealloying/additional alloying, in agreement with the study of Hejral et al using unsupported Ni–Ga nanoparticles . The behavior observed for Ni–Ga/SiO 2 contrasts what have been observed for other bimetallic catalysts (i.e., Cu–Zn, Cu–Ga, , Pd–Ga) synthesized via the same SOMC approach used in this work, where dealloying, even if partial, was always observed under CO 2 hydrogenation conditions. ,,,, Note that the absence of bulk dealloying was also observed for the Au–Zn/SiO 2 system (Au:Zn ca. 33:67) .…”
Section: Results and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results indicated that the Ni–Ga alloy nanoparticles retained their structure and composition under CO 2 hydrogenation conditions, with no evidence for dealloying/additional alloying, in agreement with the study of Hejral et al using unsupported Ni–Ga nanoparticles . The behavior observed for Ni–Ga/SiO 2 contrasts what have been observed for other bimetallic catalysts (i.e., Cu–Zn, Cu–Ga, , Pd–Ga) synthesized via the same SOMC approach used in this work, where dealloying, even if partial, was always observed under CO 2 hydrogenation conditions. ,,,, Note that the absence of bulk dealloying was also observed for the Au–Zn/SiO 2 system (Au:Zn ca. 33:67) .…”
Section: Results and Discussionsupporting
confidence: 91%
“…In that context, research efforts have been undertaken to improve Cu-based catalysts, as well as explore alternative metal-based catalysts such as Ni, Pd, and Au, ,, focusing on understanding the nature of the active sites and the role of additional metals/metal oxides, which is critical to allow for a knowledge-driven catalyst design. For example, Ga-promoted transition metal catalysts, such as Cu–Ga, Ni–Ga, and Pd–Ga, have shown promising activity for the CO 2 hydrogenation to methanol. In these catalysts, Ga was present in the form of an alloy that in many cases ,,, coexisted with oxidized Ga species under reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation